MALE CIRCUMCISION: Interpretation Debate on Judaism, The New Testament, and Health - Yusak Tanasyah; Bobby Kurnia Putrawan (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2023)
Male circumcision is often practiced across the world for a variety of reasons including health, medical necessity, beauty, tradition, or religion. Jews have practiced male circumcision since Abraham's time and continue until now. This practice is obligatory for Jewish males soon after they are born. In the New Testament, we read Paul talks about circumcision as the practice of Jewish belief, and for Christians, he said spiritual circumcision is the new law of the New Testament. Now, male circumcision is not only related to religion, and culture but connect to the health issue. The interpretation of religion, culture, and health become an interpretation debate over many years. There is Circumcision either improves or decreases male sexual function or satisfaction. It is critical to understand how male circumcision (MC), especially when performed in childhood, impacts men's sexual satisfaction and performance. The topic is also quite contentious. Our objective is to give a comprehensive study of the studies on the influence of male circumcision from Jewish, Christian, and health interpretations.